A rare case of limited granulomatosis with polyangiitis presenting as bilateral parotitis - Vandana Bandari; Sandra Apenteng; Aaradhana Kaul (European Journal of Case Reports in Internal Medicine)
Background: Granulomatosis with polyangiitis (GPA) is a rare autoimmune vasculitis affecting small and medium-sized vessels, commonly involving the respiratory tract and kidneys. Salivary gland involvement, particularly bilateral parotitis, is an uncommon presentation of GPA. Case Report: We report the case of a 38-year-old Asian male who presented with left ear pain and parotid swelling after a water park visit. Initially treated with antibiotics for suspected otitis externa, his symptoms worsened, leading to bilateral parotitis, facial palsy, and otomastoiditis. Imaging revealed parotid abscesses and lab results showed elevated antineutrophil cytoplasmic antibodies (ANCA), specifically cytoplasmic ANCA directed against proteinase 3, confirming the diagnosis of GPA. Cultures and autoimmune workups for other causes, such as Sjogren’s syndrome and immunoglobulin G4-related disease, were negative. Treatment with high-dose corticosteroids and methotrexate resulted in significant clinical improvement. Conclusion: This case highlights the importance of considering GPA in atypical presentations such as parotitis, even in the absence of renal involvement. Early diagnosis and appropriate immunosuppressive therapy are critical to prevent further complications in multisystem involvement.